Screen Semi-Slant Lightlike Submanifolds of Indefinite Kaehler Manifolds: Shiv Sharma Shukla, Akhilesh Yadav - Team, Support (Thai Journal of Mathematics, 2021)
In this paper, we introduce the notion of screen semi-slant lightlike submanifolds of indefinite Kaehler manifolds giving characterization theorem with some non-trivial examples of such submanifolds. Integrability conditions of distributions D_1, D_2 and RadTM on screen semi-slant lightlike submanifolds of an indefinite Kaehler manifold have been obtained. Further we obtain necessary and sufficient conditions for foliations determined by above distributions to be totally geodesic. We also study mixed geodesic screen semi-slant lightlike submanifolds of indefinite Kaehler manifolds.